Caracterização do óleo de carnaúba para uso como biolubrificante - Cavalcanti, Synara Lucien de Lima (2014)
Lubricant is responsible for reducing the wear on the friction protect the metal against oxidation, corrosion and dissipates excess heat, making it essential for the balance of a mechanical system, consequently prolonging the useful life of such a system. The origin of lubricating oils is usually mineral being extracted from the petroleum. But the search for a new source of production of lubricants and fuels it is necessary to meet future demands and reduce the possible environmental damage. For this reason, looking alternative means to produce certain products derived from petroleum, such as biodiesel, for example. Returning to the realm of lubricants, also one realizes this need for new raw materials for their production. Vegetable oil is a renewable resource and biodegradable, and its use entails advantages in environmental, social and economic. The development of this project aims to characterize the carnauba oil as a lubricant plant, or biolubricant. To analyze the oil carnauba tests as checking density, flash point, fire point, viscosity, viscosity, acid number, pH, copper corrosion, thermal conductivity and thermal resistivity were developed. In addition, for conducting the wear on the friction and the gradient of the system temperature, the analysis equipment is designed for wear on the friction. Based on these results, it is observed that the oil carnauba show good correlation to its application as biolubricant